Triflic Anhydride (Tf2O)-Activated Transformations of Amides, Sulfoxides and Phosphorus Oxides via Nucleophilic Trapping - Huang, Hai; Kang, Jun Yong (Synthesis, 2022)
Trifluoromethanesulfonic anhydride (Tf2O) is utilized as a strong electrophilic activator in a wide range of applications in synthetic organic chemistry, leading to the transient generation of a triflate intermediate. This versatile triflate intermediate undergoes nucleophilic trapping with diverse nucleophiles to yield novel compounds. In this review, we describe the features and applications of triflic anhydride in organic synthesis reported in the past decade, especially in amide, sulfoxide, and phosphorus oxide chemistry through electrophilic activation. A plausible mechanistic pathway for each important reaction is also discussed.1 Introduction2 Amide Chemistry2.1 Carbon Nucleophiles2.2 Hydrogen Nucleophiles2.3 Nitrogen Nucleophiles2.4 Oxygen and Sulfur Nucleophiles2.5 hosphorus Nucleophiles2.6 A Vilsmeier-Type Reagent2.7 Umpolung Reactivity in Amides3 Sulfoxide Chemistry3.1 Oxygen Nucleophiles3.2 Carbon Nucleophiles3.3 Nitrogen Nucleophiles3.4 Thionium Reagents4 Phosphorus Chemistry4.1 Hendrickson’s Reagent4.2 Diaryl Phosphine Oxides4.3 Phosphonates, Phosphates and Phosphinates5 Conclusion and Outlook
Keywords: electrophilic activation; amides; sulfoxides; phosphorus oxides; triflic anhydride; phosphonium triflate